Role for Rif1 in the checkpoint response to damaged DNA in Xenopus egg extracts - Kumar, Sanjay (Landes Bioscience, 2012)
TopBP1 is critical for both DNA replication and checkpoint regulation in vertebrate cells. In this study, we have identified Rif1 as a binding partner of TopBP1 in Xenopus egg extracts. In addition, Rif1 also interacts with both ATM and the Mre11-Rad50-Nbs1 (MRN) complex, which are key regulators of checkpoint responses to double-stranded DNA breaks (DSBs). Depletion of Rif1 from egg extracts compromises the activation of Chk1 in response to DSBs but not stalled replication forks. Removal of Rif1 also has a significant impact on the chromatin-binding behavior of key checkpoint proteins. In particular, binding of TopBP1, ATR and the MRN complex to chromatin containing DSBs is reduced in the absence of Rif1. Rif1 interacts with chromatin in a highly regulated and dynamic manner. In unperturbed egg extracts, the association of Rif1 with chromatin depends upon formation of replication forks. In the presence of DSBs, there is elevated accumulation of Rif1 on chromatin under conditions where the activation of ATM is suppressed. Taken together, these results suggest that Rif1 plays a dynamic role in the early steps of a checkpoint response to DSBs in the egg-extract system by promoting the correct accumulation of key regulators on the DNA.